Comparative analysis of trending tweets in Twitter during the year 2022 on days of public health significance - D., Diana Constance; Subbiah, Rohini; Madankumar, Parangimalai D.; Sukumaran, Aparna (International Journal Of Community Medicine And Public Health, 2023)
The use of social media in healthcare communication has expanded, public dissemination of health-related information is less common. Objective of the study was to compare the number of tweets received by public health campaigns with trending tweet and likes in twitter on those specific days. Recent posts with hashtags of nine general health and five dental public health related campaigns between 01 January 2022 to 31 December 2022 were selected from Twitter based on public health importance. We looked for top trending campaigns that had the most global reach. Descriptive statistical analysis was performed. Among the nine general health campaigns, no likes were received for five campaigns and three campaigns got likes which were greater than the trending campaigns. Among the oral health related tweets, only National tooth brushing day campaign garnered 76000 likes and none of the other oral health related tweet garnered likes. Future Twitter-based health campaigns should emphasize image-based information endorsed by a reputable organization. Further support for this message from well-known twitter users could expand the information's reach.